2020
DOI: 10.1101/2020.04.24.060376
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The anti-HIV Drug Nelfinavir Mesylate (Viracept) is a Potent Inhibitor of Cell Fusion Caused by the SARS-CoV-2 Spike (S) Glycoprotein Warranting further Evaluation as an Antiviral against COVID-19 infections

Abstract: AbstractCoronaviruses belong to a group of enveloped, positive-single stranded RNA viruses that are known to cause severe respiratory distress in animals and humans. The current SARS coronavirus-2 (SARS CoV-2) pandemic has caused more than 2,000,000 infections globally and nearly 200,000 deaths. Coronaviruses enter susceptible cells via fusion of the viral envelope with the plasma membrane and/or via fusion of the viral envelope with endosomal membranes after endocytosis of the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Molecular docking studies predicted nelfinavir binding site on SARS-CoV-2 protease (Mothay and Ramesh, 2020). Nelfinavir could also inhibit cell fusion caused by the SARS-CoV-2 S glycoprotein (https://doi.org/10.1101/2020.04.06.026476) (Musarrat et al, 2020). It also inhibits CHIKV, DENV, HCV, HSV-1, and SARS infections (https://doi.org/10.1039/C5RA14469H) (Kalu et al, 2014;Toma et al, 2009;Yamamoto et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular docking studies predicted nelfinavir binding site on SARS-CoV-2 protease (Mothay and Ramesh, 2020). Nelfinavir could also inhibit cell fusion caused by the SARS-CoV-2 S glycoprotein (https://doi.org/10.1101/2020.04.06.026476) (Musarrat et al, 2020). It also inhibits CHIKV, DENV, HCV, HSV-1, and SARS infections (https://doi.org/10.1039/C5RA14469H) (Kalu et al, 2014;Toma et al, 2009;Yamamoto et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Nelfinavir mesylate is generated as an anti-human immunodeficiency virus (HIV) protease inhibitor, originally established to be used in combination with HIV targeting antivirals through different mechanisms. With the advancement of recently developed antiviral combinations for HIV, nelfinavir mesylate reportedly inhibited severe Acute Respiratory Syndrome (SARS) replication and cytopathic effects in cell culture [15,70]. Previously, the structure and function S glycoprotein of SARS in transient transfectionmembrane fusion assessment were investigated [71,72].…”
Section: Nelfinavirmentioning
confidence: 99%
“…Previously, the structure and function S glycoprotein of SARS in transient transfectionmembrane fusion assessment were investigated [71,72]. SARS CoV-2 S (Sn) has been reported to cause profound S-mediated membrane fusion compared to the cell fusion produced by transient expression of SARS (So) [70]. The probability of binding nelfinavir to the S2 amino terminus within the S trimer was revealed by in-silico docking experiments thus; it may straightly prevent the formation of the heptadrepeat complex that results in S-mediated membrane fusion [70].…”
Section: Nelfinavirmentioning
confidence: 99%
“…Research team from National Institute of Infectious Disease of Japan found that nelfinavir is the most potent protease inhibitor against SARS-CoV-2, 3-5 times more potent than lopinavir/ritonavir (9). Several computational models also confirmed that nelfinavir can bind SARS-CoV-2 main protease (Mpro) at the Glu166 position (7,8), and this interaction is quantitatively greater than that of lopinavir and ritonavir (10). Furthermore, a more recent computational model suggested that nelfinavir can also attack the SARS-CoV-2 Spike protein, inhibiting viral entry into the cell (8).…”
Section: Introductionmentioning
confidence: 98%
“…Nelfinavir is an oral antiretroviral protease inhibitor used in the therapy and prevention of human immunodeficiency virus. In vitro data from multiple groups have shown that nelfinavir has activity against SARS-CoV-2 (7,8). Research team from National Institute of Infectious Disease of Japan found that nelfinavir is the most potent protease inhibitor against SARS-CoV-2, 3-5 times more potent than lopinavir/ritonavir (9).…”
Section: Introductionmentioning
confidence: 99%